2019
DOI: 10.1002/mds.27865
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases caudate dopamine release and ventral striatal activation in Parkinson's disease

Abstract: Background The objective of this study was to examine the effects of aerobic exercise on evoked dopamine release and activity of the ventral striatum using positron emission tomography and functional magnetic resonance imaging in Parkinson's disease (PD). Methods Thirty‐five participants were randomly allocated to a 36‐session aerobic exercise or control intervention. Each participant underwent an functional magnetic resonance imaging scan while playing a reward task before and after the intervention to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(151 citation statements)
references
References 38 publications
(96 reference statements)
2
139
0
Order By: Relevance
“…Three studies showed that motor symptoms either improved (when measured in the on-medication state) [28] or attenuated (when measured in the off-medication state) [4,23]. This was not confirmed in the eight other studies [11,24,25,27,[29][30][31]33]. However, these latter studies were generally of lower methodological quality.…”
Section: Physical Functioningmentioning
confidence: 92%
See 2 more Smart Citations
“…Three studies showed that motor symptoms either improved (when measured in the on-medication state) [28] or attenuated (when measured in the off-medication state) [4,23]. This was not confirmed in the eight other studies [11,24,25,27,[29][30][31]33]. However, these latter studies were generally of lower methodological quality.…”
Section: Physical Functioningmentioning
confidence: 92%
“…Quality assessments were compared and discussed when necessary. In total, three studies were rated with the low risk of bias [4,23,24], 10 studies with some concerns about the risk of bias [11,[25][26][27][28][29][30][31][32][33], and four studies with the high risk of bias [34][35][36][37] (Fig. 2).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable progress in the area of physical training-induced neuroplasticity effects in PD (11,54,55), though our understanding is far from complete. Studies reported that PD patient show increased serum NfL protein levels (17) compared to age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the dopamine replacement therapy is one of the most common treatment strategies for PD. Deep brain stimulation, stem cell transplantation, gene therapy, rehabilitation therapy, and other non-drug therapies also could be most used clinically [8][9][10][11][12]. Although these therapies can improve the symptoms on some extent, their role in effectively ceasing the progress of PD is unknown.…”
Section: Introductionmentioning
confidence: 99%